The role of rapid maxillary expansion in pediatric obstructive sleep apnea: Efficacy, mechanism and multidisciplinary collaboration. (February 2023) - Xie, Bintao; Zhang, Lingling; Lu, Yanqin
Abstract: This review aims to provide current knowledge about the efficacy, mechanism, and multidisciplinary collaboration of rapid maxillary expansion (RME) treatment in pediatric obstructive sleep apnea (OSA). OSA is a chronic disease characterized by progressively increasing upper airway resistance, with various symptoms and signs. Increasingly the evidence indicates that RME is a non-invasive and effective therapy option for children with OSA. Besides, the therapeutic mechanism of RME includes increasing upper airway volume, reducing nasal resistance, and changing tongue posture. Recent clinical researches and case reports also show that a multidisciplinary approach improves sleep-disordered breathing in children. Applied with adenotonsillectomy, mandibular advancement, continuous positive airway pressure, and comprehensive orthodontic treatment, RME can be more effective in recurrent or residual OSA.